Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, Dan Perilaku Belajar Terhadap Tingkat Pemahaman Akuntansi (Studi Empiris Pada Mahasiswa Program Studi S-1 Akuntansi Angkatan 2019 UPN Veteran Jawa Timur) - Hanif Respati Sudira; Dyah Ratnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Accounting education equips students with knowledge of sciences in accordance with their field of study. The level of understanding of Accounting can be seen from the theories and practices related to accounting acquired by students. The level of understanding of each student about accounting is different. The purpose of this study was to determine the effect of intellectual intelligence, emotional intelligence, and learning behavior on the level of understanding of accounting. This study uses a quantitative approach. The population in this study were accounting students, Faculty of Economics and Business, East Java Veterans National Development University. The sampling technique in this study used probability sampling with simple random sampling technique. The sample for this study was determined using the slovin formula with a 10% inaccuracy allowance of 72 respondents. The type of data used in this study is primary data from distributing questionnaires to respondents. The analysis technique used is Partial Least Square (PLS). The implication in this study is that students who have high intellectual intelligence are not necessarily able to implement it. Students must increase emotional intelligence by understanding various feelings or situations that are happening, and also students are better able to get used to an activity which can adjust their wants and needs, and can focus more on what is happening. The results of this study indicate that emotional intelligence has an influence on the level of understanding of accounting, while intellectual intelligence and learning behavior have no influence on the level of understanding of accounting. Keywords : Intellectual Intelligence, Emotional Intelligence, Learning Behavior, Level of Understanding of Accounting